SURVEI PELAKSANAAN PROSES PEMBELAJARAN PENJASORKES PADA SISWA DI SEKOLAH LUAR BIASA ( SLB ) NEGERI 2 DI KABUPATEN PEMALANG TAHUN 2014 - Duladi Lukman; Anirotul Qori'ah (Universitas Negeri Semarang, 2016)
The purpose of this study was to investigate the implementation of the learning system of physical education and health in students in special schools (SLB) N 2 in Pemalang 2014. This research method is a qualitative research, which means that the issues discussed in the research aims to create a description, picture or painting in a systematic, factual and accurate information on the facts. Results from this study can be explained that, syllabus and lesson plans are available at the school and has been modified to suit the abilities and conditions so that students can follow the lesson well. The conclusion of this study, that the teacher continues to provide motivation and reinforcement during the learning process of physical education for mentally disabled children as to provide motivation and reinforcement will increase the enthusiasm and spirit of the child.